Hubungan Antara Obesitas dengan Penghargaan Diri (Self-Esteem) pada Orang Dewasa - Annisa Salsabila Nurramadhani; Gemah Nuripah; Rizky Suganda Prawiradilaga (Bandung Conference Series: Medical Science, 2022)
Abstract. Obese people have a stigma that they are lazy and cannot control themselves which in turn can affect how they judge themselves and form their self-concept or also known as self-esteem. This study aims to analyze the relationship between obesity and self-esteem in the city of Bandung. This research design uses an observational analytic method with a cross-sectional approach. Obtained 63 adult respondents selected by purposive sampling method. Data were collected using the Rosenberg Self-Esteem Scale (RSES) questionnaire which has 10 likert items with opposite ratings based on four categories of answers. Body mass index (BMI) in subjects was calculated by researchers using the WHO's BMI calculator. Bivariate analysis with Chi-Square test using IBM SPSS version 26. The results showed that the percentage of normal-high self-esteem category in individuals with a normal BMI was 74.3% and in individuals who had a BMI Obesity 60.7%. The results of the analysis showed that there was no significant difference (p-value = 0.250) between normal BMI and obesity in terms of self-esteem. Self-esteem is influenced by many things such as the environment, friends, family, and even globalization from foreign cultures. The conclusion obtained from this research is that there is no relationship between obesity and self-esteem in adults in the city of Bandung. Abstrak. Penderita obesitas memiliki stigma bahwa mereka adalah orang malas dan tidak bisa mengontrol diri yang berikutnya dapat berpengaruh pada bagaimana mereka menilai dirinya sendiri dan membentuk konsep dirinya atau disebut juga sebagai penghargaan diri. Penelitian ini bertujuan untuk menganalisis hubungan antara obesitas dengan penghargaan diri di Kota Bandung. Rancangan penelitian ini menggunakan metode analitik observasional dengan pendekatan cross-sectional. Didapatkan 63 responden orang dewasa terpilih dengan metode purposive sampling. Data diambil dengan menggunakan kuesioner Rosenberg Self-Esteem Scale (RSES) yang memiliki 10 item likert dengan penilaian yang berkebalikan berdasarkan empat kategori jawaban. Indeks massa tubuh (IMT) pada subjek dihitung oleh peneliti menggunakan kalkulator IMT dari WHO. Analisis bivariat dengan uji Chi-Square menggunakan IBM SPSS versi 26. Hasil penelitian didapatkan persentase kategori penghargaan diri normal-tinggi pada individu yang memiliki IMT normal 74,3% dan pada individu yang memiliki IMT Obesitas 60,7%. Hasil analisis menunjukkan tidak terdapatperbedaan yang signifikan (p-value = 0,250) antara IMT normal dengan obesitas dalam hal penghargaan diri. Penghargaan diri dipengaruhi dari banyak hal seperti lingkungan, teman, keluarga, bahkan globalisasi dari budaya asing. Simpulan yang didapatkan dari penilitian ini adalah tidak terdapat hubungan antara obesitas dengan penghargaan diri pada orang dewasa di Kota Bandung.